Etika Bisnis Islam dan Maqashid al-Shariah dalam Praktik Pinjaman Online - Hardiansyah Padli; , Rahma Detik Kurningsih (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The rapid growth of financial technology (fintech), particularly online lending platforms, has expanded public access to financing through speed and convenience. However, alongside these benefits, online lending practices have generated significant ethical concerns, including excessive costs, unclear contractual terms, asymmetric power relations, and debt collection practices that may harm and psychologically pressure borrowers. This study aims to examine online lending practices from the perspective of Islamic business ethics and maqashid al-shariah, and to formulate an ethical framework for online lending oriented toward maslahah. This research employs a qualitative approach using a conceptual-analytical literature review. Data were collected from reputable national and international journal articles, classical and contemporary Islamic economics literature, and relevant regulatory documents, and analyzed through content analysis and conceptual synthesis. The findings indicate that many online lending practices do not fully reflect the principles of Islamic business ethics and the objectives of maqashid al-shariah, particularly in terms of protecting wealth, life, and intellect. The study concludes that online lending cannot be justified solely by formal legality or technological efficiency, but must be substantively evaluated based on justice, contractual transparency, social responsibility, and public welfare. This study contributes by offering an ethical framework for evaluating and developing fair and sharia-compliant fintech lending.